Precast concrete construction for the building industry - Leow, Geok Mui. (2008)
This dissertation provides a study of the precast technologies adopted in the building industry. The project introduces the various precast components, which are widely adopted in the construction industry, highlighting the advantages and disadvantages, and the erection procedures and safety aspects of precasrt building construction.